Pulmonary Drug Delivery: A Promising Approach - ND Shah, VV Shah, ND Chivate (Journal of Applied Pharmaceutical Science)
Pulmonary drug delivery has attracted tremendous scientific and biomedical interest in recent years and has progressed considerably within the context of local treatment for lung diseases, by virtue of enhanced local targeting and reduced systemic side effects with the administration of minute drug dosages. Furthermore, with the high surface area and permeability of the lung, the 21st century has seen a paradigm shift to inhaled therapy for systemic use. But the pulmonary tract tends to be considered as very promising and attractive route for the administration of active substances intended to treat local pulmonary e.g., asthma, chronic obstructive pulmonary disease (COPD), microbial infections) as well as systemic diseases. (e.g., diabetes) Recent progress within biotechnology has generated a group of novel protein and peptide drugs to which administration to the respiratory tract, to obtain systemic delivery seems advantageous compared to e.g. parenteral or gastrointestinal administration (tablets, capsules etc.). The low metabolic activity in the lungs allows systemic delivery without liver passage Hence lung is an attractive environment for biomolecules, which are highly susceptible to enzymatic degradation in the gastrointestinal tract (ventricle and guts) as well as hepatic degradation (first pass metabolism).
Keywords: Pulmonary drug delivery,Dry powder for inhalation,Asthma,Chronicobstructive pulmonary disease.